Modeling Hydrocarbon Generation of Deeply Buried Type Ⅲ Kerogen: A Study on Gas and Oil Potential of Lishui Sag, East China Sea Shelf Basin - Zhang, Jinliang; Li, Yang; Liu, Jinshui; Yan, Xue; Li, Lianjie; Shen, Wenlong (Frontiers in Earth Science, 2021)
Based on gold-tube pyrolysis experiments of deeply-buried Type Ⅲ kerogen, the hydrocarbon generation model and hydrocarbon potential are investigated in the Lishui Sag. With the discussion of genetic mechanism of differences in hydrocarbon generation characteristics of the kerogen, some suggestions are put forward for the classification of kerogen types of source rocks with mixed organic matter sources. The hydrocarbon generated from the source rocks of the Lingfeng formation and Yueguifeng formation are dominated by natural gases with little oil in the West sub sag, and the hydrocarbon generation model of the Lingfeng formation is similar to that of Yueguifeng formation, but the gas potential of Lingfeng formation is higher than Yueguifeng formation. The hydrocarbon potential of the Yueguifeng formation in the East sub sag is much higher than the West sub sag, and it has considerable oil potential. Macerals diversity of source rocks is responsible for the difference of hydrocarbon generation characteristics for Type Ⅲ kerogen in the Lishui sag. It is not rigorous to evaluate hydrocarbon potential of kerogen only based on pyrolysis parameters. Application of kerogen type index (KTI) can improve the accuracy of the classification of kerogen types with mixed organic matter sources. Although according to the classical kerogen classification template, the selected samples belong to type III kerogen. In this paper, the selected samples were further divided into type III and type II/III based on the KTI value. Type III kerogen (0.5 ≤ KTI< 1.5) mainly produces gas, while the type II/III kerogen (1.5 ≤ KTI < 5) mainly produces gas, but its oil potential is higher than that of type III kerogen.